Keratoacanthoma, Verruca Vulgaris Arising over Porokeratosis of Mibelli : A New Association - Asaduzzaman, ATM; Rahman Rahat, Mohammad Lutfur; Uddin, Mohammad Jamal; Hena Chowdhury, Mohammod Abu; Haque, AKM Rejaul (Medicine Today, 2021)
Introduction: This case report highlighting the presence of keratoacanthoma and verruca vulgaris over the lesion of porokeratosis of mibelli. Case Report: In this case a 50-year-old housewife came with large well-defined asymptomatic plaque over the upper part of back of the trunk for last 10 years. After evaluation we got the presence of keratoacanthoma and verruca vulgaris on the plaque of porokeratosis of mibelli. Discussion: Porokeratosis is a clonal expansion of keratinocytes. Among the neoplasm squmous cell carcinoma (SCC) is the most commonly reported malignancy in porokeratosis. But in our case we didn’t find lesion of SCC. Porokeratosis of Mibelli, Keratoacanthoma and Verruca vulgaris have an association with human papilloma virus(HPV). This eithopathogenesis may be related to our clinical finding. Conclusion: There were reporting of squmous cell carcinoma or keratoacanthoma on Porokeratosis of Mibelli. But in our case we found both Keratoacanthoma and Verruca Vulgaris over Porokeratosis of Mibelli. Medicine Today 2021 Vol.33(2): 172-175